2019
DOI: 10.1002/ccd.28149
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and clinical response to transseptal mitral valve‐in‐valve and valve‐in‐ring

Abstract: Objective To understand the clinical and hemodynamic response of patients with stenotic versus regurgitant prosthetic mitral valve degeneration to transseptal transcatheter mitral valve‐in‐ring/‐valve replacement (TMVR). Background Patients with prosthetic mitral valve repair/replacement failure frequently present high‐risk surgical challenges. TMVR has been employed as an alternative to surgery. Methods Forty‐four patients with stenotic/regurgitant degeneration of prior prosthetic mitral annuloplasty and repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(48 reference statements)
1
5
0
1
Order By: Relevance
“…These studies have demonstrated the overall safety and feasibility of TVIV and TVIR, including significant improvement in hemodynamics, great success in reducing severe MR, and a 30-day and 6-month mortality rate of 8% to 14% and 24%, respectively. [108][109][110][111][112][113][114][115] Longterm outcomes of TVIV and TVIR were assessed in a recent study, which confirmed previous clinical outcomes, and found all-cause mortality at 1 year and 2 years to be 21% and 36%, respectively. 116 This study also considered TMVI for patients with severe MAC (TMVI-MAC) who are not surgical candidates.…”
Section: Transcatheter Valve-in-valve Implantationmentioning
confidence: 71%
“…These studies have demonstrated the overall safety and feasibility of TVIV and TVIR, including significant improvement in hemodynamics, great success in reducing severe MR, and a 30-day and 6-month mortality rate of 8% to 14% and 24%, respectively. [108][109][110][111][112][113][114][115] Longterm outcomes of TVIV and TVIR were assessed in a recent study, which confirmed previous clinical outcomes, and found all-cause mortality at 1 year and 2 years to be 21% and 36%, respectively. 116 This study also considered TMVI for patients with severe MAC (TMVI-MAC) who are not surgical candidates.…”
Section: Transcatheter Valve-in-valve Implantationmentioning
confidence: 71%
“…To further evaluate hemodynamic response to TMVR in relation of underlying mitral pathology, we compared hemodynamic data between the current study cohort of valve‐in‐mitral annular calcification with a control group of patients who underwent valve‐in‐valve/ring TMVR for prosthetic mitral stenosis with baseline mean prosthetic mitral gradient >10 mmHg. The details of the valve‐in‐valve/ring cohort have been reported previously 9 . Statistical significance was defined a priori as p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Improvement in left atrial pressure during transcatheter mitral valve repair has been shown to correlate with degree of functional improvement during follow‐up 8 . TMVR has been shown to yield favorable hemodynamic improvement in patients undergoing valve‐in‐valve or valve‐in‐ring procedures 9 . However, the hemodynamic response to TMVR may differ for patients with severe mitral annular calcification due to the associated left ventricular and left atrial abnormalities, and varying degrees of intrinsic mitral valve stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing invasive hemodynamic monitoring signaled successful closure with a substantial overall reduction in intracardiac pressures and documented thereby significant resolution of the patient's prior severe prosthetic mitral stenosis (Figures ). Normalization of such pressures, however, was not achieved, underscoring the simultaneous presence of other contributing factors (e.g., reduced LA compliance) …”
Section: Transcatheter Mitral Valve Interventionmentioning
confidence: 96%